Detection of Inhibitor Content in Transformer Oil at Wavelengths below 1000 nm - Thiviyanathan V.A.; Jern Ker P.; Leong Y.S.; Afini Fauzi N.; Jamaludin M.Z.; Looe H.M.; Lo C.K. (Institute of Electrical and Electronics Engineers Inc., 2023)
Photodetectors; Power transformers; Signal processing; Spectrophotometers; Continuous monitoring; Inhibitor content; Main transformer; Optical characterization; Optical detection methods; Power transmission and distributions; Silicon photo-detector; Transformer oil samples; Oil filled transformers